2014
DOI: 10.1145/2532169
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution Tensor Decompositions with Mode Hierarchies

Abstract: Tensors (multidimensional arrays) are widely used for representing high-order dimensional data, in applications ranging from social networks, sensor data, and Internet traffic. Multiway data analysis techniques, in particular tensor decompositions, allow extraction of hidden correlations among multiway data and thus are key components of many data analysis frameworks. Intuitively, these algorithms can be thought of as multiway clustering schemes, which consider multiple facets of the data in identifying cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Multi-scale methods can interpolate from low-resolution to highresolution [23,25,30] or operate first on one part of the tensor and then progressively generalize to the whole tensor [29]. For example, Schifanella et al [25] exploits extra domain knowledge and develops a multiresolution method to improve CP and Tucker decomposition. Song et al [29] imputes the tensor from a small corner and gradually increases on all modes by multi-aspect streaming.…”
Section: Multi-scale and Randomized Methodsmentioning
confidence: 99%
“…Multi-scale methods can interpolate from low-resolution to highresolution [23,25,30] or operate first on one part of the tensor and then progressively generalize to the whole tensor [29]. For example, Schifanella et al [25] exploits extra domain knowledge and develops a multiresolution method to improve CP and Tucker decomposition. Song et al [29] imputes the tensor from a small corner and gradually increases on all modes by multi-aspect streaming.…”
Section: Multi-scale and Randomized Methodsmentioning
confidence: 99%
“…epiDMS, a novel epidemic simulation data management system software framework [26], aims to address the key challenges underlying large epidemic spread simulations, which, today, hinder real-time and continuous analysis and decision-making during ongoing outbreaks. Unlike other dynamic modeling platforms, such as Berkeley Madonna [27], the services provided by epiDMS include (a) storage and indexing of large-ensemble simulation data sets and the corresponding models and (b) search and analysis of ensemble simulation data sets to enable ensemble-based decision support [28][29][30].…”
Section: Epidms Overview and Use Scenariomentioning
confidence: 99%
“…The second part of the proposal concerns the use of advanced DM techniques such as tensor-based representations (of semantics, rather than words) by embodying syntactic roles (subjects, modifiers, verbs, and arguments) into its dimensions (see Figure 1). The complexity of algorithms for tensors is a major challenge in this level, although recent re-search has shown that background information can improve this issue (Schifanella et al, 2014). Advanced data analysis techniques on tensors allow operations that are suitable for the aim of this ongoing research project.…”
Section: Distributional Analysis Of Semanticsmentioning
confidence: 99%